2022
DOI: 10.1038/s41598-022-20129-3
|View full text |Cite
|
Sign up to set email alerts
|

A functional neuroimaging study of self-other processing alterations in atypical developmental trajectories of psychotic-like experiences

Abstract: Self-disturbances constitute a hallmark of psychosis, but it remains unclear whether these alterations are present in at-risk populations, and therefore their role in the development of psychosis has yet to be confirmed. The present study addressed this question by measuring neural correlates of self-other processing in youth belonging to three developmental trajectories of psychotic experiences. Eighty-six youths were recruited from a longitudinal cohort of over 3800 adolescents based on their trajectories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…model of psychosis according to which auditory verbal hallucinations (AVH) result from the combination of inhibitory and self-monitoring deficits 7 . Of note, self-monitoring deficits have been noted in a sub-sample of the CoVenture cohort experiencing high PLEs frequency 45 . These findings also echo previous results in schizophrenia patients who display a higher frequency of go/no-go commission errors, which is in turn associated with a worse total-PANSS and general psychopathology scores 5 .…”
Section: Discussionmentioning
confidence: 93%
“…model of psychosis according to which auditory verbal hallucinations (AVH) result from the combination of inhibitory and self-monitoring deficits 7 . Of note, self-monitoring deficits have been noted in a sub-sample of the CoVenture cohort experiencing high PLEs frequency 45 . These findings also echo previous results in schizophrenia patients who display a higher frequency of go/no-go commission errors, which is in turn associated with a worse total-PANSS and general psychopathology scores 5 .…”
Section: Discussionmentioning
confidence: 93%
“…Functional magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) are common neuroimaging modalities that assess the interactions between distinct brain regions at functional and structural levels, respectively. Previous functional MRI studies have demonstrated that dysfunctional connectivity of the CCTCC is associated with impaired cognitive performance 39 , 40 and clinical manifestations, including positive and negative symptoms 41 43 and self-experience disturbances 44 , 45 , in patients with schizophrenia. DTI studies have indicated that aberrations in white matter tracts connecting the cerebrum and cerebellum correlate with poor cognitive functioning 46 49 and clinical symptom severity 50 , 51 .…”
Section: Introductionmentioning
confidence: 99%